Quadratic equations have the general form:

ax2 + bx + c = 0

When factorising a quadratic they are usually into a pair of brackets.

For example: x+ 5x + 6 = 0 (x + 2)(x + 3) = 0

This is useful, because once they are factorised, we can solve them easily (i.e. find out what x must be). 

We have two numbers (each of the two brackets) which when multiplied together, make 0. You can make 0 by at least one of the brackets being zero (since any number multiplied by zero is zero! e.g. 2 x 0 = 0, 56 x 0 = 0, 0 x 3 x 320 = 0. )

So, whatever x is, each bracket must add up to 0 for the result to = 0.

For the first bracket, x must be -2, since (-2 + 2)(-2 + 3) = 0 x 1 = 0.

For the second bracket, x must be -3, since (-3 + 2)(-3 + 3) = -1 x 0 = 0.

Improve this description

Nothing in this section yet. Why not help us get started?

Add a Video Resource

Nothing in this section yet. Why not help us get started?

Improve the Test Questions

Related Topics

Requires a knowledge of…

2Simple software

Related Questions

All related questions